Design and implementation of a power amplifier rf at 1.748GHz- Area of engineering - Moreno-Rubio, Jorge Julián; Amaya-Medina, Will; Hernández, Libardo Enrique (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
Class F Amplifiers has high power efficiency as main characteristic, which makes them useful intransmission circuits. This paper contains the design, simulation and implementation of an amplifier RF class F at 1.748 GHz, its importance, application and design. The implementation was realized by using of microstrip lines with RF 35 subtrate of the Taconic company. The obtained results are shown and its behavior is evaluated.